Tuple space enhancements for mobile middleware. (1st January 2014) - De, Suddhasil; Nandi, Sukumar; Goswami, Diganta
Tuple space-based mobile middleware (TSMM) is affected by two elementary factors of the tuple space model, viz. the tuple / antituple structure and the tuple space structure. The tuple/antituple structure influences application design as well as simplicity and flexibility of TSMM, while the tuple space structure regulates its performance and scalability. In existing TSMM, the unordered tuple/antituple structure improves simplicity and flexibility, while degrades performance and scalability due to the additional overhead in tuple generation and lookup. Again, the sequential tuple space structure in existing TSMM produces considerable performance overhead for the tuple-reading and -consuming primitives. This paper proposes two enhancements in the tuple space model for TSMM: 1) enhancement in the unordered tuple/antituple structure for reducing the additional overhead as well as preserving the simplicity and flexibility of TSMM; and, 2) introduction of the enhanced tuple space structure for further reducing the overhead of the tuple-reading and -consuming primitives. Analysis and experiments confirm the superiority of TSMM with proposed enhancements over existing ones.